2015
DOI: 10.7567/jjap.54.031001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of valence-band splitting in InN by low-temperature photoreflectance spectroscopy

Abstract: Temperature-dependent photoluminescence (PL) and photoreflectance (PR) spectroscopy and room-temperature Raman spectroscopy and X-ray diffraction have been utilized to investigate the optical properties, electron concentration, crystalline quality, and electronic band structures, especially valence-band splittings, of InN films grown by plasma-assisted molecular beam epitaxy (PAMBE) and metal–organic chemical vapor deposition (MOCVD). The smaller thermal activation energies imply the PAMBE-grown InN film exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…This ordering of the valence bands corresponds to the positive SOC, determined by the positive values of two SOC parameters and , which are referred to as the SOC constants along the c axis of the wurtzite lattice and in the plane perpendicular to the c axis, respectively. The reported values of and in InN and GaN, obtained from ab-initio band structure calculations and experiments, were in the range from 1 to 25 meV 21 23 . The positive SOC in GaN and InN was taken into account so far in the study of the TPT in InN/GaN and InGaN/GaN QWs 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This ordering of the valence bands corresponds to the positive SOC, determined by the positive values of two SOC parameters and , which are referred to as the SOC constants along the c axis of the wurtzite lattice and in the plane perpendicular to the c axis, respectively. The reported values of and in InN and GaN, obtained from ab-initio band structure calculations and experiments, were in the range from 1 to 25 meV 21 23 . The positive SOC in GaN and InN was taken into account so far in the study of the TPT in InN/GaN and InGaN/GaN QWs 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Кроме электронных InAs и InSb из полупроводниковых соединений A 3 B 5 такая же ситуация с приповерхностным изгибом зон и возникновением на поверхности обогащенного электронами слоя наблюдается в InN, ФО которого измерялось в [122,123]. Замечено, что для данного материала приповерхностное электрическое поле In-полярной поверхности InN меньше, чем Nполярной [124].…”
Section: арсенид индия (Inas)unclassified
“…This phenomenon, called the polarization-induced TPT, was initially proposed for InN/GaN QWs with L TI qw equal to four atomic monolayers (MLs) [24]. The predicted values of E TI 2Dg in these structures depend significantly on the assumed intrinsic SOI in InN, which is still under scientific debate [26][27][28][29]. It was found that E TI 2Dg can reach 5 meV when a positive SOI of the order of a few meV is assumed in InN, or it can be about 1.25 meV when a negative SOI in InN is considered [24][25][26].…”
Section: Introductionmentioning
confidence: 99%